Risk assessment of medically assisted reproduction and advanced maternal ages in the development of Prader–Willi syndrome due to UPD(15)mat. Issue 5 (10th December 2015) - Matsubara, K.; Murakami, N.; Fukami, M.; Kagami, M.; Nagai, T.; Ogata, T.
Abstract : Recent studies have suggested that disomic oocyte‐mediated uniparental disomy 15 (UPD(15)mat) is increased in patients with Prader–Willi syndrome (PWS) born after medically assisted reproduction (MAR). However, it remains unknown whether the increase is primarily due to MAR procedure itself or advanced maternal childbearing ages as a predisposing factor for the disomic oocyte production. To examine this matter, we studied 122 naturally conceived PWS patients (PWS‐NC group) and 13 MAR‐conceived patients (PWS‐MAR group). The relative frequency of disomic oocyte‐mediated UPD(15)mat was significantly higher in PWS‐MAR group than in PWS‐NC group (7/13 vs 20/122, p = 0.0045), and the maternal childbearing ages were significantly higher in PWS‐MAR group than in PWS‐NC group [median (range), 38 (26–45) vs 30 (19–42), p = 0.0015]. However, the logistic regression analysis revealed no significant association between the occurrence of disomic oocyte‐mediated UPD(15)mat and MAR, after adjusting for childbearing age (p = 0.25). Consistent with this, while the frequency of assisted reproductive technology (ART)‐conceived livebirths was higher in the PWS patients than in the Japanese general population (6.4% vs 1.1%, p = 0.00018), the distribution of childbearing ages was significantly skewed to the increased ages in the PWS patients (p < 2.2 × 10 −16 ). These results argue against a positive association of MAR procedure itself with the development of UPD(15)mat.